Exogenous factors impact on bacterial-microalgal growth and chromophoric dissolved organic matter: a case study of Chrysotila dentata and Marinobacter hydrocarbonoclasticus - Wang, Xueru; Sun, Jun (Frontiers in Marine Science, 2024)
The relationship between Chrysolia dentata and bacteria that play an important role in the carbon cycle is complex yet closely intertwined. However, there is still limited knowledge about how phytoplankton interacts with heterotrophic bacteria under external influences. The transformation and processing of dissolved organic matter (DOM) by epiphytic bacteria for phytoplankton especially, under vitamin B12 (VB12) and abscisic acid (ABA) introducing have rarely been investigated. In this experiment, Marinobacter hydrocarbonoclasticus (CA6) was cultured with Chrysotila dentata to investigate growth and DOM release and transformation under the influence of VB12 and ABA. Three-dimensional (3D)-EEM, combined with fluorescence regional integration and the peak selecting method, was used to obtain fluorescent peaks (B, T, A, and C) and four indexes for DOM analysis. Our findings indicate that the incubation of CA6 significantly enhances the release of protein-like components (peak T) and humic-like components (peak C) during the incubation period. However, 100 μg/L VB12 or abscisic acid does not promote axenic microalgae growth or release of C. dentata-derived DOM. However, they have different effects on C. dentata-CA6 growth and the derived DOM. Abscisic acid can facilitate steady growth of both C. dentata and CA6 cells while enhancing the amounts of humic-like components. Conversely, VB12 inhibits the growth of CA6 and results in a rapid decrease in protein-like signal, but it does not significantly enhance C. dentata growth or the transformation of DOM. This indicates that ABA can support stable co-grown of microalgal and bacteria in a water environment, while VB12 may hinder CA6 bacterial growth, resulting in a less stable co-cultured environment. This study uncovers and verifies the impact of exogenous factors and heterotrophic bacteria in the growth of microalgae, underlining their role in transforming and generating algae-derived dissolved organic matter (DOM) within laboratory settings.